2008
DOI: 10.1007/s00264-007-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in periprosthetic bone remodelling after redesigning an anatomic cementless stem

Abstract: The aim of this prospective cohort study was to determine the densitometric relevance of minor design modifications of a cementless stem designed to improve proximal load transfer. We used a prospective cohort study with densitometric analysis over a five-year period of two groups of patients with primary osteoarthritis. The first group, 56 hips, received the first version of the ABG stem (ABG-I); the second group, 54 hips, had the ABG-II stem. The results obtained with the ABG-I stem showed a decrease of bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
(37 reference statements)
3
20
0
Order By: Relevance
“…Bone remodelling with signs of proximal femoral stress shielding around the ABG I femoral component has been extensively reported in the literature [17,[24][25][26][27]. Recently, using both finite element analysis and DEXA, comparative studies have indicated that the ABG II femoral component was more effective than the first generation in terms of proximal femoral bone stock atrophy preservation [31,32]. No bone-implant radiolucency was observed in the areas coated with hydroxyapatite, whereas reactive lines related to distal elasticity and to medullary diaphyseal bone reaction closed to the polished tip were only observed in Gruen Zones 3, 4, and 5 in less than 6% of cases.…”
Section: Discussionmentioning
confidence: 98%
“…Bone remodelling with signs of proximal femoral stress shielding around the ABG I femoral component has been extensively reported in the literature [17,[24][25][26][27]. Recently, using both finite element analysis and DEXA, comparative studies have indicated that the ABG II femoral component was more effective than the first generation in terms of proximal femoral bone stock atrophy preservation [31,32]. No bone-implant radiolucency was observed in the areas coated with hydroxyapatite, whereas reactive lines related to distal elasticity and to medullary diaphyseal bone reaction closed to the polished tip were only observed in Gruen Zones 3, 4, and 5 in less than 6% of cases.…”
Section: Discussionmentioning
confidence: 98%
“…39 DXA studies of the ABG stem showed a reduction of 16% and 17% in BMD three and five years, respectively, after hip replacement. 18,40 Some of the initial bone loss could be a result of intra-operative rasping and reaming. 38 The importance of the early resorption of bone within two years is not known, but according to the Norwegian arthroplasty register both the Unique and the ABG-I stems have a survival rate of more than 96% after ten years, using aseptic loosening as the endpoint.…”
Section: Fig 6amentioning
confidence: 99%
“…In both studies the surgical technique, post-operative rehabilitation program, densitometry studies and statistical analysis were identical (Panisello et al, 2009b). The study confirmed less proximal atrophy, therefore one could ask if the new design has effectively improved the load transfer conditions in the proximal femur, producing less stress-shielding.…”
Section: Application To the Behaviour Of Hip Prostheses Cementless Smentioning
confidence: 64%
“…Prior to the development of our FE models several long-term studies of bone remodeling after the implantation of two different cementless stems, ABG I and ABG II, were performed Panisello et al, 2009a;Panisello et al, 2009b). These studies were performed using DXA, a technique that allows an accurate assessment of bone density losses in the different Gruen zones.…”
Section: Resultsmentioning
confidence: 99%